Digital Libraries The Era of Big Data and Data Science 16th Italian Research Conference on Digital Libraries, IRCDL 2020 (Springer Nature, 2020)
16th Italian Research Conference on Digital Libraries, IRCDL 2020, Bari, Italy, January 30-31, 2020, Proceedings
English
Keywords: Reference, Information and Interdisciplinary subjects; Digital libraries